2021
DOI: 10.1016/j.jaac.2020.09.022
|View full text |Cite
|
Sign up to set email alerts
|

The DSM-5 Limited Prosocial Emotions Specifier for Conduct Disorder: Comorbid Problems, Prognosis, and Antecedents

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“… 1. To illustrate the overlap between dimensions of psychopathy and criteria for childhood disruptive behavior disorders, a recent study by Colins et al (2020) administered a commonly used measure of psychopathic traits in children and adolescents and reported that the correlation between impulsive lifestyle dimension of psychopathy with a measure of ADHD symptoms was r = .84 ( p < .001). Furthermore, five of the nine items used to assess the interpersonal dimension of psychopathy were related to lying and conning other people (i.e., “Lies often to avoid problems,” “seems to lie more than other children of the same age,” often lies to get what he/she wants,” “to frequently lie seems to be completely normal for him/her,” “to get people to do what he/she wants, he/she often finds it efficient to con them”).…”
mentioning
confidence: 99%
“… 1. To illustrate the overlap between dimensions of psychopathy and criteria for childhood disruptive behavior disorders, a recent study by Colins et al (2020) administered a commonly used measure of psychopathic traits in children and adolescents and reported that the correlation between impulsive lifestyle dimension of psychopathy with a measure of ADHD symptoms was r = .84 ( p < .001). Furthermore, five of the nine items used to assess the interpersonal dimension of psychopathy were related to lying and conning other people (i.e., “Lies often to avoid problems,” “seems to lie more than other children of the same age,” often lies to get what he/she wants,” “to frequently lie seems to be completely normal for him/her,” “to get people to do what he/she wants, he/she often finds it efficient to con them”).…”
mentioning
confidence: 99%
“…Specifically, one aspect of prosociality, that is limited prosocial emotions, was recently introduced as a specifier of conduct disorder to the DSM-5 and ICD-11 (Colins et al, 2021). Limited prosocial emotions are a key feature of callous-unemotional traits (a precursor or marker of psychopathic traits) which have been linked to difficulties with associating harmful behaviours with negative emotional cues from the environment, leading to children failing to recognise that their behaviour may harm others (Colins et al, 2021). While children with low CU traits would modulate their own behaviours in response to cues from their environment, children with high CU traits are likely to miss out on the modulation of their behaviours, putting them at risk for the development of continuous and severe behavioural issues (Waller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it may be that the bidirectional associations between conduct problems and prosociality observed here reflect the strong links between conduct problems and psychopathy. Specifically, one aspect of prosociality, that is limited prosocial emotions, was recently introduced as a specifier of conduct disorder to the DSM-5 and ICD-11 (Colins et al, 2021 ). Limited prosocial emotions are a key feature of callous-unemotional traits (a precursor or marker of psychopathic traits) which have been linked to difficulties with associating harmful behaviours with negative emotional cues from the environment, leading to children failing to recognise that their behaviour may harm others (Colins et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We considered several child-specific and peer processes as potential external validators of identified profiles. Specifically, we examined CU behaviors, given that the presence of CU traits with conduct problems may represent a distinct subtype of youth who are at increased risk for a more severe and persistent trajectory of conduct problems and antisocial behavior, higher levels of negative contextual correlates, and less responsiveness to intervention than youth with conduct problems without CU traits (Colins, Fanti, & Andershed, 2020;Fanti & Kimonis, 2013;Frick, 2012;Pardini, Stepp, Hipwell, Stouthamer-Loeber, & Loeber, 2012). More specifically for the present study, the relations among conduct problems and the neurobiological and cognitive factors that we considered often vary based on the presence of CU traits, suggesting that CU traits may indicate differential risk (Blair, 2015;Frick, 2012;Hwang et al, 2016;Lozier et al, 2014;Martin-Key et al, 2018).…”
Section: Potential External Validators For Conduct Problem Profilesmentioning
confidence: 99%